SISTEM PEMANTAUAN DISTRIBUSI STOK PADA MANAJEMEN RANTAI PEMASOK MENGGUNAKAN PENDEKATAN CONTINUOUS REVIEW DAN METODE SINGLE EXPONENTIAL SMOOTHING - , Husni Angriani A; , Dr. Azhari S.N., M.T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Determining the time and the appropriate number of stock ordered by distributor and supplier to fulfill the request of customer is a complex problem in supply chain management. This problem affects the process of supplying for supplier, the process distribution for distributor and the selling process for retailers hampered. This research developed a monitoring stock model which was integrated with continuous review approach for determining time for reorder point, so that supplier, distributor and retailer enabled to know time to reorder which is suitable with the sales data. The proposed model used single exponential smoothing method to forecast quantity order. Forecasting quantity order aimed to know how many stocks which were supposed to be ordered to fulfill the demand of final customer. The result of this research shows that the developed system is able to monitor stock from retailer, distributor, and supplier. The developed system is able to determine time of reordering using continuous review approach and to decide the appropriate number of ordering goods on retailer, distributor, and supplier. The testing system used the data of sales made during a month which was implemented into the system. The results of the data which was put into the system showed that the cost of inventories at the retailers and distributors were too big. Those were because there was too much inventory on each side which did not match with consumer demand, so it could cause risk to all parties.